2020
DOI: 10.21203/rs.3.rs-42890/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficiency of Online Course of Medical Statistics in Nanjing Medical University During the COVID-19 Epidemic

Abstract: Background: To analyze the online course efficiency of a combined mode of Massive Open Online Course (MOOC) micro-video and E-learning platform in Nanjing Medical University during the COVID-19 epidemic. Methods: We developed a new questionnaire to assess the efficiency of online teaching of medical statistics in Nanjing Medical University. This investigation enrolled students participating in the online course of medical statistics from January 2020 to June 2020. The “Questionnaire Star” electronic questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…As shown in Supplement 1, a total of 15,473 medical science students were enrolled in the 24 studies [1,3,12,[19][20][21][22][23][24][25][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The mean±standard deviation age of the participants was 20.84±2.06 years, and 58.23% were women.…”
Section: Study Characteristics and Results Of Individual Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…As shown in Supplement 1, a total of 15,473 medical science students were enrolled in the 24 studies [1,3,12,[19][20][21][22][23][24][25][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The mean±standard deviation age of the participants was 20.84±2.06 years, and 58.23% were women.…”
Section: Study Characteristics and Results Of Individual Studiesmentioning
confidence: 99%
“…Of the participants, 73.45% were studying clinical medicine. Of the studies included in this systematic review, 14 studies [19][20][21]24,25,[29][30][31]33,[36][37][38][39][40]] reported e-learning modalities, 16 studies [3,19,20,[23][24][25]29,30,32,33,[36][37][38][39][40]42] reported platforms used in e-learning, and 10 studies [12,19,22,25,29,[32][33][34][35]40] reported devices used in e-learning. The studies included in this systematic review were conducted in India (n=5) [1,12,30,39,40], China (n=3) [20,33,34], Saudi Arabia (n=3)…”
Section: Study Characteristics and Results Of Individual Studiesmentioning
confidence: 99%
See 3 more Smart Citations